A novel geometric parameter to evaluate the effects of block form on solar radiation towards sustainable urban design. (September 2022) - Li, Jingjin; Wang, Yuxiao; Xia, Yang
Highlights: The increase of density has a greater impact on the solar radiation of sites than that of buildings. Proposed a new parameter Block Surface Ratio to predict the solar radiation on the block. Blocks with lower BSR should be preferentially selected to obtain more solar radiation. Seasonal changes has different influences on the solar radiation of sites and buildings. The U-shape and Court 1 types should be given priority when promoting solar panels. Abstract: The utilization of solar energy plays an important role in coping with global climate change and low-carbon development. Solar radiation in the urban environment is affected by urban block geometry. The relationship between solar radiation and urban block geometry in Nanjing, which has a temperate climate, was studied in this paper. Two hundred generic models in eight typologies that represent a diverse range of urban block density and forms were examined. Seven geometric parameters and three periods of solar radiation on urban blocks, including a year, one typical week in summer, and one typical week in winter, were calculated. Four aspects of solar radiation were investigated at the block scale: (1) the relationship between urban density and solar radiation, (2) the solar radiation on different layout types of urban blocks, (3) the seasonal effect of solar radiation on buildings and open spaces, and (4) the potential of solar photovoltaic technology utilization in block surface. In addition to the obvious negative effect of density, this study indicated that the solar radiation on buildings and surrounding open spaces was significantly influenced by block form. Block surface ratios are the most influential geometric parameters for the solar radiation on buildings, while open spaces are more affected by sky view factor. The seasonal effect on solar radiation presents a much greater impact on open spaces than on buildings. This study highlights the important role that urban geometry plays in the on-site solar energy harvesting.